BOUNDS FOR VOLUMES OF SUB-LEVEL SETS OF POLYNOMIALS AND APPLICATIONS - Ta, Le Loi (Trường Đại học Đà Lạt, 2023)
In this paper, we present some explicit exponents in the estimates for the volumes of sub-level sets of polynomials on bounded sets and applications to the decay of oscillatory integrals and the convergence of singular integrals.